Health service providers in Somalia: their readiness to provide malaria case-management - Noor, A; Rage, I; Moonen, B; Snow, R (BioMed Central, 2009)
Background: Studies have highlighted the inadequacies of the public health sector in sub-Saharan African countries in providing appropriate malaria case management. The readiness of the public health sector to provide malaria case-management in Somalia, a country where there has been no functioning central government for almost two decades, was investigated. Methods: Three districts were purposively sampled in each of the two self-declared states of Puntland and Somaliland and the south-central region of Somalia, in April-November 2007. A survey and mapping of all public and private health service providers was undertaken. Information was recorded on services provided, types of anti-malarial drugs used and stock, numbers and qualifications of staff, sources of financial support and presence of malaria diagnostic services, new treatment guidelines and job aides for malaria case-management. All settlements were mapped and a semi-quantitative approach was used to estimate their population size. Distances from settlements to public health services were computed. Results: There were 45 public health facilities, 227 public health professionals, and 194 private pharmacies for approximately 0.67 million people in the three districts. The median distance to public health facilities was 6 km. 62.3% of public health facilities prescribed the nationally recommended anti-malarial drug and 37.7% prescribed chloroquine as first-line therapy. 66.7% of public facilities did not have in stock the recommended first-line malaria therapy. Diagnosis of malaria using rapid diagnostic tests (RDT) or microscopy was performed routinely in over 90% of the recommended public facilities but only 50% of these had RDT in stock at the time of survey. National treatment guidelines were available in 31.3% of public health facilities recommended by the national strategy. Only 8.8% of the private pharmacies prescribed artesunate plus sulphadoxine/pyrimethamine, while 53.1% prescribed chloroquine as first-line therapy. 31.4% of private pharmacies also provided malaria diagnosis using RDT of microscopy. Conclusion: Geographic access to public health sector is relatively low and there were major shortages of appropriate guidelines, anti-malarials and diagnostic tests required for appropriate malaria case management. Efforts to strengthen the readiness of the health sector in Somalia to provide malaria case management should improve availability of drugs and diagnostic kits; provide appropriate information and training; and engage and regulate the private sector to scale up malaria control.